KERJASAMA PEMERINTAH DAN MASYARAKAT DALAM PEMBANGUNAN DESA DI DESA PARIA KABUPATEN PINRANG - Alpian Muhtar; Fatmawati Fatmawati; Samsir Rahim (JPPM: Journal of Public Policy and Management, 2022)
This study aimed to find out the form of government and community cooperation in the development of Paria Village. The research method used a qualitative research method. Data collection techniques through observation, interviews, and documentation. Research informants were 10 people by using purposive sampling technique. The data validation technique used source, technique, and time triangulation. Data analysis techniques used data reduction techniques, data presentation, and conclusions making. The results of the study showed that the form of cooperation between the government and the community of Paria Village used spontaneous cooperation, during the implementation of community service; direct cooperation, the implementation of the seminar. The inhibiting factor was the government and the community were not able to apply traditional forms of cooperation due to the lack of awareness of the importance of traditional cooperation in village development and there were differences of opinion when the implementation of a cooperation was underway. Meanwhile, the supporting factors were the level of community and government participation in village development was very high, due to the level of concern between the community and the government towards the conditions and directions of future village development and the emergence of a sense of mutual support for each other, impartial and fair to all. an activity related to village development.